Is there any gender-specific impact in the treatment of patients with basal cell carcinoma in the head and neck region? - L. Hartlieb; P. Funovits; W. Pipam; M. Rab (JPRAS Open, 2023)
Summary: Background: There are no current studies concerning gender-specific impact on the treatment of BCCs. We performed a retrospective analysis with the aim of showing that selection of treatment by physician and patients’ evaluation concerning quality of life and aesthetic outcome has a gender-specific impact. Methods: Overall, 47 patients treated by excision of BCC from the head and neck region at our department from 2015 to 2020 were included. Defects were closed via flap, split-thickness skin graft. or primary closure. Pain, scar quality, patient satisfaction and quality of life were ascertained by the Skin Cancer Index (SCI), the Basal and Squamous Cell Carcinoma Quality of Life (BaSQoL) questionnaire, Patient and Observer Scar Assessment Scale (POSASv2.0EN) and Vancouver Scar Scale (VSS). Results: Women received significantly more flaps than split-thickness skin grafts (p = 0.025). The coverage method was independent of surgeons’ gender.Patient's POSAS were higher in women (p = 0.087), and observer's POSAS (p = 0.229) and VSS (p = 0.7) showed no significant difference between genders.SCI and BaSQoL scores showed that women are significantly more critical than men after BCC treatment (SCI p = 0; BaSQoL p = 0.022). Furthermore, dermatological follow-up frequency was significantly higher in women (p = 0.035). Conclusion: We determined the gender-specific impacts on the treatment of patients with BCCs regarding methods of closure, post-interventional dermatological follow-ups, quality of life, scar quality, and overall patient satisfaction. No difference in scar quality was found when assessed by physicians.